The frequency of the fragile X chromosome among schoolchildren in Coventry. Issue 5 (October 1986) - Webb, T P; Bundey, S; Thake, A; Todd, J
Abstract : A population study has been carried out among schoolchildren in the City of Coventry in order to ascertain the frequency of mental retardation associated with the fragile X chromosome. The prevalence of the fragile X mental retardation syndrome in the 11 to 16 year age group (the age of greatest ascertainment) was about 1.0 per 1, 000 and therefore indicates that the syndrome is a major cause of mental retardation.